The essence and content of scientific research methodology - O. Mozolev; O. Polishchuk (Journal of Education, Health and Sport)
The article analyzes the essence and content of the concepts "methodology", "methods of scientific research". The content of general and special methods of conducting scientific research is disclosed. It has been established that the methodology of scientific research is a conceptual statement of the content, purpose, and methods of research that allow obtaining the most objective, systematized and accurate information about phenomena and processes. The methodology systematizes the methods, methods and methods of learning objective reality, ensuring the reliability of the obtained knowledge about the object of research, their compliance with the subject of research, and is also a means of substantiating the results and conclusions of the conducted scientific research.